Analisis Evaluasi Program Sekolah Adiwiyata di SMP Negeri 47 Surabaya - Ucik Rachmawati; Sabrina Fitri Jasmine; Jihan Tsaabitah Farhah (Pusat Riset dan Inovasi Nasional, 2023)
This research was carried out by researchers with the aim of being able to evaluate and explain how the implementation of the adiwiyata program at SMP Negeri 47 Surabaya. This research uses evaluative research type. This study uses the CIPP evaluation model which includes evaluation of Context, Input, Process, and Product through the implementation of the adiwiyata program at SMPN 47 Surabaya which will be assessed for the program. Data collection techniques used by researchers are observing, interviewing and documenting. Meanwhile, data analysis was carried out using data condensation, data presentation, and data verification. In testing the validity of the data, researchers also used source triangulation and technique triangulation. The results of this study show that the context component at SMP Negeri 47 Surabaya has met the criteria for fulfilling the adiwiyata school program components in the form of vision, mission and school goals already in the 2013 Curriculum which contains efforts to manage the environment. The input component shows the source of funds used, namely from BOS and BOSDA for plant maintenance. The process component contains the learning and maintenance process for SARPRAS. As well as the product component contains many works or products produced through school creativity activities.